KEPADATAN DAN POLA PENYEBARAN Ficus spp. DI STASIUN PENELITIAN CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG KALIMANTAN BARAT - Hadi, Sumi; Rafdinal, Rafdinal; Linda, Riza (Universitas Tanjungpura, 2019)
Ficus is key species that commonly lives in tropical region because of its ability to bear fruit year around, thus so many kind of Ficus that become source of food and habitat to animals. The aim of the research to determine the density and distribution pattern of Ficus spp. at Research Station of Gunung Palung National Park in May until June 2018. The observation of Ficus spp. is done by random sampling method on five different locations, there are lowland granite, warmth, sands stone, freshwater swamp and alluvial land. The result showed that there are 4 species of Ficus with density ranges 16-60 individuals/ha and the distributions patterns are uniform and grouped.